The Key Strategic Leadership Roles of School Principals in Enhancing Educational Quality in the Digital Era - Nur Izatul Yazidah; Nur Nabilla Sarah; Sulaiman; Krista Alisa Meyliani; Wahyu Setiyaningrum; Widyatmike Gede Mulawarman; Akhmad (Poltanesa, 2025)
The rapid advancement of digital technologies has reshaped the governance, learning ecology, and performance expectations within contemporary educational institutions. This study investigates the strategic leadership exercised by school principals in orchestrating digital transformation as a pathway for improving educational quality. Adopting a descriptive qualitative design, data were collected through semi-structured interviews, systematic observations, and document analysis to construct a comprehensive understanding of leadership practices in a digitally evolving school environment. The findings indicate that the principal articulates a coherent and future-oriented digital vision (score 85) that effectively aligns institutional goals with technological innovation. Change management strategies (score 78) have facilitated gradual yet meaningful pedagogical shifts, although disparities in teachers’ digital readiness persist. The utilization of a Learning Management System (LMS) represents the most robust dimension of implementation (score 88), enhancing instructional efficiency, data transparency, and supervisory oversight. The school’s emerging culture of innovation (score 80) further reinforces digital integration, albeit with uneven participation across teaching staff. Teachers’ digital competence (score 72), however, remains a critical developmental area requiring sustained professional learning opportunities. Overall, the study underscores that strategic leadership is a pivotal determinant of successful digital transformation, highlighting the necessity for visionary direction, evidence-informed decision-making, and continuous capacity building in advancing educational quality in the digital era.